Gene expression profiles of adult peripheral and cord blood mononuclear cells altered by lipopolysaccharide - Koch, Lutz; Linderkamp, Otwin; Ittrich, Carina; Benner, Axel; Pöschl, Johannes (Neonatology, 2008)
Background: Neonatal Gram-negative sepsis is often characterized by a fulminant clinical course, compared to adults, resulting in higher morbidity and mortality. Genome-wide gene expression analysis can provide insights into the molecular alterations in sepsis. Objectives: To evaluate in vitro activation of the neonatal and adult immune system, gene expression patterns were compared in mononuclear cells from cord (CBMNC) and adult peripheral blood (APBMNC). Methods: To better understand the influence of early molecular signals on the effects of sepsis, Affymetrix gene profiling (8,475 genes) was done on RNA isolated from CBMNC and APBMNC without and after incubation with 100 ng/ml lipopolysaccharide (LPS). Results: We demonstrated significant alterations in the expression of 108 CBMNC and APBMNC genes compared with basal levels, 188 significant changes in CBMNC and 97 in APBMNC, including cytokines, chemokines and immunoregulatory genes. Furthermore, we found 5 genes showing a significant interaction effect between cell type and LPS stimulation, including tumor necrosis factor receptor superfamily, member 6 (FAS), absent in melanoma 2, malic enzyme 1, hemoglobin Ε 1, and trans-prenyltransferase. Conclusions: These results provide further support for a marked difference in the pathogenesis of neonatal and adult sepsis and may stimulate additional studies to investigate some of the altered genes as potential new targets for diagnostic tools and therapeutic strategies.
Gesehen am 12.09.2023